2008
DOI: 10.1590/s0004-282x2008000400001
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor MR imaging evaluation of the corpus callosum of patients with multiple sclerosis

Abstract: -Objective: To evaluate the fractional anisotropy (FA) values of the normal-appearing white matter of the corpus callosum (CC) in patients with relapsing-remitting multiple sclerosis (MS). Method: Fifty-seven patients with diagnosis of relapsing-remitting MS and 47 age-and gender-matched controls were studied. A conventional MR imaging protocol and a DTI sequence were performed. One neuroradiologist placed the regions of interest (ROIs) in the FA maps in five different portions of the normal-apearing CC (rostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
4
10
0
Order By: Relevance
“…Multiple sclerosis (MS), a demyelinating disease affecting the central nervous system, is characterized by inflammatory demyelinating foci in the brain white matter with variable axonal damage (Huizinga et al, 2008;Rueda et al, 2008). Although its etiology is still scarcely understood, the composition of plaques, immunogenetic background, responses to immunomodulation, and data from animal models suggest that MS is mediated by myelin-specific CD4 ϩ T cells (Lu, 2006;Sonobe et al, 2007;Elyaman et al, 2008;Sabatino et al, 2008).…”
mentioning
confidence: 99%
“…Multiple sclerosis (MS), a demyelinating disease affecting the central nervous system, is characterized by inflammatory demyelinating foci in the brain white matter with variable axonal damage (Huizinga et al, 2008;Rueda et al, 2008). Although its etiology is still scarcely understood, the composition of plaques, immunogenetic background, responses to immunomodulation, and data from animal models suggest that MS is mediated by myelin-specific CD4 ϩ T cells (Lu, 2006;Sonobe et al, 2007;Elyaman et al, 2008;Sabatino et al, 2008).…”
mentioning
confidence: 99%
“…[29][30][31][32][33] Sigal et al [11] used DTI to investigate CC integrity in MS patients and age matched controls. In agreement with other studies, [15,26,28,31] MS patients had significant reduction in CC 's FA compared with control group in all subregion of CC, indicating axonal loss and dysfunction in callosal fibers. Most recent studies agree on the fact that in MS patients all MRI indices and parameters are altered pathologically especially in the CC structure.…”
Section: In Multiple Sclerosis Mrimentioning
confidence: 99%
“…Some authors observed FA decreases predominantly in the body of the CC, [6][7][8] with an insignificant trend in the splenium, 7,8 and no significant changes in the genu. 7 Therefore, some researchers reported that CC abnormalities might be a sensitive marker of MS. 9,10 CIS, suggestive of MS, as typically the earliest clinical expression of many patients with MS, 11 has received a great deal of attention from recent clinical research.…”
mentioning
confidence: 99%
“…Abnormal CC integrity (reduced FA or increased MD) is also a common finding in MS using DTI. [4][5][6][7][8] Moreover, some DTI studies have found different change patterns in the subdivisions of the CC.…”
mentioning
confidence: 99%
See 1 more Smart Citation